2007
DOI: 10.1063/1.2737377
|View full text |Cite
|
Sign up to set email alerts
|

CdSe nanowires with controllable growth orientations

Abstract: Epitaxial growths of CdSe nanowires with controllable orientations by metal organic chemical vapor deposition are obtained. Scanning electron microscopy reveals that they preferred to align along different orientations when grown on different GaAs surfaces. The geometrical relationship between their orientations and the substrates can further be changed by changing the growth temperature. They all grow along the ⟨110⟩ direction of the substrates at 480°C, but along the ⟨111⟩ direction at 500°C. X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The modulation of nanowire orientation through growth temperature change has been reported by several groups. Shan et al found that temperature controlled the preferred growth direction of wurtzite CdSe nanowires grown on GaAs substrates using MOCVD [113]. When grown at 480 • C, most CdSe nanowires grew along the substrate 1 1 0 direction whereas at a higher temperature of 500 • C the nanowires preferred the 1 1 1 direction, in both cases irrespective of the substrate orientation.…”
Section: 41mentioning
confidence: 99%
“…The modulation of nanowire orientation through growth temperature change has been reported by several groups. Shan et al found that temperature controlled the preferred growth direction of wurtzite CdSe nanowires grown on GaAs substrates using MOCVD [113]. When grown at 480 • C, most CdSe nanowires grew along the substrate 1 1 0 direction whereas at a higher temperature of 500 • C the nanowires preferred the 1 1 1 direction, in both cases irrespective of the substrate orientation.…”
Section: 41mentioning
confidence: 99%
“…special properties and the potential applications in many fields [1][2][3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…INTRODUCTION Semiconductor nanowires (NWs), such as ZnO, [1][2][3][4] CdS, 5,6 CdSe, 7-10 GaN [11][12][13] NWs, have attracted a lot of attention in the past 20 years because of their superior characteristics in magnetic, optical, and electrical properties. Especially, many CdSe low-dimensional structures, such as nanowires [7][8][9][10] and quantum dots (QDs), [14][15][16] have been fabricated in the experiment.…”
mentioning
confidence: 99%